PRE-RETIREMENT PLANNING AND COUNSELLING NEEDS OF LECTURERS OF TERTIARY INSTITUTIONS IN SOKOTO STATE - Abubakar, Halima Sa'adiya (Sokoto Educational Review, 2011)
The main purpose of the study was to examine the preretirement planning and counselling needs of lecturers in tertiary institutions in Sokoto state. The sample was drawn from the total number of lecturers of tertiary institutions in Sokoto state. A total number of 384 were selected from four tertiary institutions in the state. Two adopted a set of questionnaires were used, they were Pre-retirement Planning Questionnaire and Counselling Needs Questionnaire. Three hypotheses were generated and tested in the study. In the analyses, of findings, t-test, ANOVA and Pearson Product Moment Correlation Coefficient statistical procedures were used. Result of the study revealed that lecturers of tertiary institutions in Sokoto differ in their pre-retirement plan on the bases of age and occupational status but did not differ with respect to gender. The result also revealed that there is no significant difference in counselling needs on the basis of age, sex and occupational status. A positive relationship was displayed in the relationship between pre-retirement plan and counselling needs. Since retirement is an inevitable pill that any civil sen ’ant has to swallow, it is, therefore, of paramount importance to counsel lecturers on preparation for retirement. Some of recommendations given are, that sensitization programmes, workshops and seminars are organised to enlighten the civil servants on retirement issues. Trained counsellors with requisite knowledge and qualification are to be appointed to counsel the workforce on retirement.